Fine-tuning sugar content in strawberry - Xing, Sinian; Chen, Kunling; Zhu, Haocheng; Zhang, Rui; Zhang, Huawei; Li, Bingbing; Gao, Caixia (Genome Biology, 2020)
Fine-tuning quantitative traits for continuous subtle phenotypes is highly advantageous. We engineer the highly conserved upstream open reading frame (uORF) of FvebZIPs1.1 in strawberry ( Fragaria vesca ), using base editor A3A-PBE. Seven novel alleles are generated. Sugar content of the homozygous T1 mutant lines is 33.9–83.6% higher than that of the wild-type. We also recover a series of transgene-free mutants with 35 novel genotypes containing a continuum of sugar content. All the novel genotypes could be immediately fixed in subsequent generations by asexual reproduction. Genome editing coupled with asexual reproduction offers tremendous opportunities for quantitative trait improvement.